Echocardiographic Heart Changes in Pregnancies Complicated with Gestation Hypertension and Preeclampsia - I., Kjaev; D., Milkovski; D., Karadjova; S., Atansova Kjaeva; A., Daneva; J., Kjaeva Nicichka; R., Spasova; G., Kocoski (International Journal of Innovative Research in Medical Science, 2019)
Introduction: Echocardiography as an imaging method is increasingly being used in obstetrics in the management of hemodynamic changes which occur in normal but also in pregnancies with gestational hypertension/preeclampsia. Aim: The aim of the study is to show that some of the heart changes in pregnancies complicated with gestational hypertension and preeclampsia are abnormal and further follow up of these patients is needed. Methods: A total of 81 patients were enrolled in the study. The patients were further divided in two groups. Pregnant women with gestational hypertension or preeclampsia (51) and a control group of normotensive pregnancies (30). A total of 3 echocardiograph exam were made, the first upon entry in the study (28 -34 g.w), the second 2 weeks after delivery and the last 6 months after delivery. Results and discussion: We found several statistically significant results that involve the IVS, PWLV, LKM, left chamber hypertrophy and diastolic function. Diastolic dysfunction usually shows up before systolic dysfunction in the evolution of ischemic/hypertensive cardiovascular disease and is of prognostic value in predicting long term cardiovascular morbidity. The changes seen 6 months after delivery on our last control mean that those changes are permanent and need further prevention strategies. Conclusion: From the noninvasive methods echocardiography is the most favorable method in identifying structural changes and functional changes in pregnancies with hypertension. Echocardiography allows fast, reproducible information and is both safe for mother and fetus.